Designing Android-Based National University News Portal Application with First In First Out (FIFO) Method: Designing Android-Based National University News Portal Application with First In First Out (FIFO) Method - Muhammad Farhan Adistyra; Agung Triayudi; Endah Tri Esthi (Institute of Computer Science (IOCS), 2020)
The study discusses the creation of an Android-based Internet news portal dedicated to the internals around the National University campus using the PHP Framework CodeIgniter (CI) and MySql databases. This news Portal is designed using Unified modeling Language. This news portal is created inspired by news portal sites that have many benefits to operate. This news Portal serves as a means for the public information media environment of the campus, especially for students at the National University, because the number of students very large reaches almost 5000 students. Media information is not available to meet the needs of students who want the speed and currency of information about the campus. This need can be met with media that can move fast and on a large scale. This news portal site contains the latest news about the National University, which includes formal and informal news. Considering this news site will add information and insights to the newsreader